2007
DOI: 10.1124/jpet.107.124768
|View full text |Cite
|
Sign up to set email alerts
|

A Global Drug Inhibition Pattern for the Human ATP-Binding Cassette Transporter Breast Cancer Resistance Protein (ABCG2)

Abstract: In this article, we explore the entire structural space of registered drugs to obtain a global model for the inhibition of the drug efflux transporter breast cancer resistance protein (BCRP; ABCG2). For this purpose, the inhibitory effect of 123 structurally diverse drugs and drug-like compounds on mitoxantrone efflux was studied in Saos-2 cells transfected with human wild-type (Arg482) BCRP. The search for BCRP inhibitors throughout the drug-like chemical space resulted in the identification of 29 previously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
103
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(117 citation statements)
references
References 38 publications
12
103
1
1
Order By: Relevance
“…A pharmacophore model was generated using 28 inhibitors in the training set. The pharmacophore was described by two hydrophobic features and one hydrogen bond acceptor, confirming the QSAR results (34).…”
Section: Structurally Unrelated Compoundssupporting
confidence: 72%
See 2 more Smart Citations
“…A pharmacophore model was generated using 28 inhibitors in the training set. The pharmacophore was described by two hydrophobic features and one hydrogen bond acceptor, confirming the QSAR results (34).…”
Section: Structurally Unrelated Compoundssupporting
confidence: 72%
“…Lipophilicity, expressed as log D 7.4 was present in another model to predict ABCG2 inhibitors. The authors suggest a log D cutoff of 0.5, above which there is an increased likelihood of a compound-inhibiting ABCG2 (34). Though lipophilicity has been shown to be a good predictor of ABCG2 inhibition in some studies, other investigators have not found this descriptor to be significant (16,27).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several attempts were made to establish SAR for BCRP interaction, however, many analysis methods were based on the datasets of inhibitors Matsson et al 2007;Matsson et al 2009;Nicolle et al 2009). Yoshikawa et al studied BCRP substrate specificity of 14 camptothecin (CPT) analogues, and noted that CPT analogues that showed ATP-dependent transport in BCRPoverexpressing membrane vesicles possess one -hydroxy or -amino group (Yoshikawa et al 2004).…”
Section: Breast Cancer Resistance Protein (Bcrp)mentioning
confidence: 99%
“…Az utóbbi években számos publikáció született amelyek tárgyát ABCG2 inhibitorok azonosítása képezete. [30,31] …”
Section: Az Abcg Alcsaládunclassified